Essays in macroeconomic modelling with frictions and rigidities - Luk, S (2014)
This thesis presents three dynamic stochastic general equilibrium models to answer three macroeconomic questions. In each model, I impose one or more frictions or constraints and analyse how these frictions affect macroeconomic dynamics. Chapter 2 studies the coordination of fiscal and monetary policies under optimal commitment and discretion policies under a New Keynesian framework. The chapter shows that when there is indexation in price setting which depends on the lagged output gap as in Steinsson (2003), under the optimal commitment policy, both fiscal and monetary policies have active roles in inflation stabilisation, even although debt follows a unit-root process. Under the optimal discretion policy, both fiscal and monetary policies have active roles in inflation stabilisation to drive debt back to the pre-shock level, consistent with Leith and Wren-Lewis (2008). Extending the model to include capital accumulation does not alter these results. Chapter 3 presents a microfounded two-country model of global imbalances and debt deleveraging. During global imbalances a sustained rise in saving in one country can lead to a worldwide fall in the interest rates and an accumulation of debt in the other country. When an ensuing deleveraging shock occurs as a result of the global financial crisis, the interest rates are forced further down. I show that in the presence of a liquidity trap the deleveraging country may face a combination of a large fall in output, deflation and real exchange rate appreciation, as a result of debt deflation. Chapter 4 adds a highly-leveraged financial sector to the Ramsey model and shows that this augments the macroeconomic effects of aggregate productivity shocks. My model is built on the financial-accelerator approach of Bernanke, Gertler and Gilchrist (BGG), in which leveraged goods-producers borrow from a competitive financial sector. In this chapter, by contrast, financial institutions are leveraged and subject to idiosyncratic productivity shocks. They obtain funds by paying an interest rate above the risk free rate, and this risk premium is anti-cyclical, and so amplifies the shocks. My parameterisation, based on US data, is one in which the leverage of the financial sector is two and a half times that of the goods-producers in the BGG model. This causes a much more significant augmentation of aggregate productivity shocks than that found in the BGG model.